Employing a Single-Screw Expander in an Organic Rankine Cycle with Liquid Flooded Expansion and Internal Regeneration. (September 2017) - Ziviani, Davide; Gusev, Sergei; Schuessler, Stefan; Achaichia, Abdennacer; Braun, James E.; Groll, Eckhard A.; De Paepe, Michel; van den Broek, Martijn
Abstract: Positive displacement expanders are proven to be cost-effective in the low to medium power range for Organic Rankine Cycle (ORC) systems. Among the different types of volumetric expanders, the screw-type presents a favorable combination of relatively high internal volume ratio (up to 7) and isentropic efficiency (up to 80%) with respect to the optimal pressure ratio at which sub-critical ORCs operate. In particular, single-screw expanders have shown some potential due to their symmetric and balanced configuration that decreases the loads on the bearings. A comprehensive characterization of this type of machine with two working fluids, i.e., SES36 and R245fa, has been carried out in a previous work [1]. Based on the experimental work, friction losses and internal leakages were found detrimental to the expander performance. As the expander requires lubrication during operation, flooded expansion can be beneficial to reduce such losses as well as to improve the expansion process toward a quasi-isothermal behavior. A thermodynamic cycle model has been developed to evaluate the potential improvements on the thermodynamic performance of organic Rankine cycle with flooded expansion and internal regeneration. A semi-empirical model of the expander is included which accounts for the effects of internal volume ratio. The results from the cycle model have used to design an ORC test setup with an independent lubricant oil loop and internal regeneration. The new test rig will be used validate the trends obtained with the cycle model and to further characterize the single-screw expander. The working fluid employed is R1233zd(E) as a replacement for R245fa.